Irreducible second and third metatarsophalangeal dislocation: a rare case report - Arnaya, Agung K.; Karna, Made B.; Asmara, Anak A. G. Y.; Meregawa, Putu F. (International Journal of Research in Medical Sciences, 2021)
Metatarsophalangeal (MTP) articulations are complex structures that are prone to sprains, subluxations, and dislocations. MTP dislocations are an uncommon but well documented and problematic orthopaedic injury. Once the diagnosis is certain, the dislocation should be reduced as soon as possible. Immediate reduction of the dislocation can limit numerous complications. A 24-year-old male patients came to emergency department of Sanglah Hospital with 2nd and 3rd MTP joint dislocation. Patient treated with open reduction and immobilization with pinning for 2nd and 3rd metatarsal. After several attempt of closed reduction, the dislocation can be reduce with open reduction and immobilization with k wire, after 4 weeks k wire was removed without any complication and patient can walk normally. Irreducible metatarsophalangeal dislocation of the lesser toes is unusual with third toe was the most commonly affected, followed by the second, fourth, and fifth toes. Radiographs are very useful for diagnose. Multiple procedures have been created to attempt to reduce and stabilize the MP joint. According to other studies, Kirschner wires were also only used in unstable dislocations. In this case, dorsal surgical approach is the most commonly chosen method to reduce the irreducible metatarsophalangeal joint dislocations of the lesser toes. When irreducible dislocation found and closed reduction is initially unsuccessful, we recommend a dorsal surgical approach to open reduction and using Kirschner wires for unstable dislocations.